FAO international conference on nutrition - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
The International Conference on Nutrition (ICN) to be held in Rome in December 1992 is a major component of FAO's activities. It will be the first international conference of its kind and will be organized jointly by FAO, the World Health...